2015
DOI: 10.1089/jmf.2014.3287
|View full text |Cite
|
Sign up to set email alerts
|

Olive Leaf Extract Elevates Hepatic PPARαmRNA Expression and Improves Serum Lipid Profiles in Ovariectomized Rats

Abstract: We hypothesized that olive leaf extract might alleviate dyslipidemia resulting from estrogen deficiency. Serum lipid profile and mRNA expression of the related genes in the liver and adipose tissue were analyzed after providing olive leaf extract (200 or 400 mg/kg body weight; n = 7 for each group) to ovariectomized rats for 10 weeks. After 10 weeks' administration, the rats in the olive leaf extract-administered groups showed significantly lower levels of serum triglyceride and verylow-density lipoprotein (VL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
(26 reference statements)
3
10
0
1
Order By: Relevance
“…In a study supporting these results, it was found that daily 20 mL olive leaf extract supplementation given to 29 healthy male participants changed expression level of early growth response protein 1, cyclooxygenase-2, and inhibitor of DNA binding 3 genes in peripheral blood mononuclear cells [47]. A study conducted with ovariectomized rats showed that olive leaf extract supplementation at the doses of 200 or 400 mg/kg body weight decreased serum triglyceride level particularly at high doses [48]. Furthermore, it was determined that 1-10 µg/mL concentration of oleuropein and hydroxytyrosol extracts inhibited ROS and protected cardiomyocytes against toxicity and carbonyl stress induced by 4-hydroxynonenal [13].…”
Section: Lipidemia and Cardiovascular Effectsmentioning
confidence: 86%
See 1 more Smart Citation
“…In a study supporting these results, it was found that daily 20 mL olive leaf extract supplementation given to 29 healthy male participants changed expression level of early growth response protein 1, cyclooxygenase-2, and inhibitor of DNA binding 3 genes in peripheral blood mononuclear cells [47]. A study conducted with ovariectomized rats showed that olive leaf extract supplementation at the doses of 200 or 400 mg/kg body weight decreased serum triglyceride level particularly at high doses [48]. Furthermore, it was determined that 1-10 µg/mL concentration of oleuropein and hydroxytyrosol extracts inhibited ROS and protected cardiomyocytes against toxicity and carbonyl stress induced by 4-hydroxynonenal [13].…”
Section: Lipidemia and Cardiovascular Effectsmentioning
confidence: 86%
“…Potential effects of olive leaf on lipid metabolism and inflammation emerge by means of metabolic pathways and inflammationrelated genes [13,[47][48][49][50]. In a study supporting these results, it was found that daily 20 mL olive leaf extract supplementation given to 29 healthy male participants changed expression level of early growth response protein 1, cyclooxygenase-2, and inhibitor of DNA binding 3 genes in peripheral blood mononuclear cells [47].…”
Section: Lipidemia and Cardiovascular Effectsmentioning
confidence: 86%
“…Ayrıca yüksek dozda zeytin yaprağı ekstresi alımının serum östradiol seviyesini anlamlı ölçüde arttırdığı belirtilmiştir. 34 24 tavşan üzerinde yapılan başka bir çalışmada yüksek yağlı diyet verilen ve oleuropein destekli normal diyet verilen tavşanlara 6 haftalık bir ça-lışma sonucunda serum trigliserid, total kolesterol, LDL ve HDL düzeyi ile malonaldehit seviyeleri karşılaştırılmıştır. Aynı zamanda 6 haftanın sonunda aterosklerotik lezyonlar ve intima kalınlı-ğına bakılmıştır.…”
Section: Somova Ve Arknın (2003) Yaptığı Bir çAlışmadaunclassified
“…It is suggested that fenofibrate significantly decreases VLDL secretion in male Wistar Unilever rats fed the diets containing fructose [78]. Exposure of ovariectomized rats to olive leaf extract for 10 weeks has been shown to lower plasma VLDL-cholesterol (VLDL-C) levels by upregulating PPARα mRNA expression [79]. In a Brazilian elderly population, C allele of PPARα is associated with lower plasma VLDL-C levels as compared to G allele, indicating a protective role for the PPARα C allele in reducing cardiovascular disease risks [80].…”
Section: Pparα Regulates Vldl Metabolismmentioning
confidence: 99%